Application of an independent dose calculation software for estimating the impact of inter-fractional setup shifts in Helical Tomotherapy treatments - Dzintars, Erik; Papanikolaou, Nikos; Mavroidis, Panayiotis; Sadeghi, Amir; Stathakis, Sotirios (Physica medica, 2013)
The purpose of this study is to validate the capability of in-house independent point dose calculation software to be used as a second check for Helical Tomotherapy treatment plans. The software performed its calculations in homogenous conditions (using the Cheese phantom, which is a cylindrical phantom with radius 15 cm and length 18 cm) using a factor-based algorithm. Fifty patients, who were treated for pelvic (10), prostate (14), lung (10), head & neck (12) and brain (4) cancers, were used. Based on the individual patient kVCT images and the pretreatment MVCT images for each treatment fraction, the corresponding daily patient setup shifts in the IEC-X, IEC-Y, and IEC-Z directions were registered. For each patient, the registered fractional setup shifts were grouped into systematic and random shifts. The average systematic dosimetric variations showed small dose deviation for the different cancer types (1.0%–3.0%) compared to the planned dose. Of the fifty patients, only three had percent differences larger than 5%. The average random dosimetric variations showed relatively small dose deviations (0.2%–1.1%) compared to the planned dose. None of the patients had percent differences larger than 5%. By examining the individual fractions of each patient, it is observed that only in 31 out of 1358 fractions the percent differences exceeded the border of 5%. These results indicate that the overall dosimetric impact from systematic and random variations is small and that the software is a capable platform for independent point dose validation for the Helical Tomotherapy modality.